Hypertrophic cardiomyopathy with apical aneurysm: a case of catheter and surgical therapy of sustained monomorphic ventricular tachycardia. Issue 5 (May 1997) - Mantica, M.; Della Bella, P.; Arena, V.
Abstract : The case is presented of a patient with hypertrophic cardiomyopathy, midventricular obstruction, apical aneurysm, and very frequent episodes of sustained monomorphic ventricular tachycardia (VT) unresponsive to common antiarrhythmic drugs. Left ventricular catheter mapping during sinus rhythm suggested the presence of an extensively scarred apical region; early fractionated ECGs were recorded at the neck of the aneurysm during monomorphic VT, suggesting a possible role of this region as VT substrate. Radiofrequency delivery at these sites stopped the VT and it was no longer inducible; however, it spontaneously recurred the following day. An apical aneurysmectomy, guided by the results of catheter mapping, was performed and was successful in preventing arrhythmic recurrences during 12 months' follow up.